Organization of Bachelor’s Independent Work on «Theory and Methods of Forming Elementary Mathematical Ideas» - Kit, Anna; Gryndii, Iryna (Pedagogical Discourse, 2013)
Article highlights problems concerning organization of bachelor’s independent work on «Theory and methods of forming elementary mathematical ideas» on the II educational qualifying Bachelor’s degree in the process of their professional preparation. Different researcher’s approaches disclose the definition of the term independent work of students; article also accents attention on objects, types and forms of student’s independent work. Methodical recommendations on organization of student’s independent work in the course study are given.